PROTECTIVE EFFECT OF HELYCHRISUM PLICATUM EXTRACTS ON ANTIOXIDANT DEFENCE STATUS IN CCL4-INDUCED HEPATOTOXICITY IN RATS - Panovska, T. K.; Kulevanova, S.; Bogdanova, M. (African Journal of Traditional, Complementary and Alternative Medicines, 2009)
This paper reports a study in which antioxidative and hepatoprotective activity of H. plicatum extracts in in vitro and in vivo conditions were tested. Phytochemical screening (HPLC) of H. plicatum from Macedonia revealed the presence of apigenin and naringenin as free aglycones and glycosides of apigenin, naringenin, quercetin and kaempferol in the flowers as well as quercetin and luteolin glycosides and free luteolin in stems and leaves. The antioxidative effect was investigated using three methods: evaluation of the free radical scavenging capacity (DPPH method), inhibition of hydroxyl radical production and protection of beta-carotene-linoleic acid system. The hepatoprotective activity was investigated using CCl4-induced liver damage model on rats. The extracts under investigation showed radical scavenging activity with IC50 value of 6 to 11 mg/ml. The extracts were capable to react with OH radical with inhibition of its production ranged between 33-58%. The high preventive activity against the bleaching of beta-carotene (15-49% of initial value after 120 minutes) was also observed. The antioxidative activity of the extracts was compared with that of luteolin, quercetin, BHA, BHT and sylimarin. In in vivo studies, the biochemical parameters in groups treated with H. plicatum extracts at a dose of 25 mg/kg showed significantly different value than that of the CCl4-treated group. The liver biopsy of all experimental rat groups treated with H. plicatum extracts showed significant restoration of normal histomorphological pattern of liver cells. Results of this study suggest that H. plicatum represents a natural source with antioxidant and hepatoprotective potential.